ความหนาของวัสดุพิมพ์ปากอัลจิเนตจากถาดพิมพ์ปากไร้ฟันต้นแบบ : ในห้องปฏิบัติการ - ทัดดาว นิตยวรรธนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
Objective: To search for the method of making the upper and lower edentulous prototype model in order to make the upper and lower edentulous prototype trays. Then, test the upper and lower edentulous prototype trays by investigate thickness of alginate impression. Material and Methods: 4 sizes of the upper and lower edentulous prototype models have been fabricated from the width, length and height of edentulous replicated master model from Yaowapha Saimai’s Mast thesis, Chulalongkorn University, 2003 "Size classification of residual ridges in a group of Thais." Then, 4 sizes of the upper and lower edentulous prototype trays have been fabricated from that models with 3 millimeters space relief for impression material. The trays have been tested by taking alginate impression on the replicated master models which were classified in the same size with the trays. 11 models were random picked up as the sample size excepted the extra large upper models which used 10 models and the extra large lower models which used only 3 models depend upon the limitation of the sample size in each group. File with rubber stop and digital veneer caliper were used to measure the thickness of alginate impression. The reference points of measurement in upper impression were 26 positions and in lower impression were 43 positions. Then, the alginate impression thickness were analyzed by frequency distribution analysis and described the result. Compared to 9 specialists in Prosthodontic’s opinion which stated that the suitable alginate impression thickness were 3 to 5 millimeters. Result: 4 sizes of upper and lower edentulous prototype models and trays can be fabricated by the method in this research. The result has been found that 51.16 percent of upper replicated master model impressions and 16.67 percent of lower replicated master model impressions had the thickness of alginate within 3 5 millimeters over 50 percent of the reference points of measurement.